Regeneração e as três ecologias de Guattari: exploração e experimentação para o desenvolvimento do design estratégico - Garcia, Natalí Abreu (Universidade do Vale do Rio dos Sinos, 2022)
In contrast with the hegemonic ways of apprehending and approaching reality, we see the emergence of the Regenerative Sustainability paradigm, which emerges from an ecological worldview. This new paradigm proposes a counterpoint to Cartesian, mechanistic and reductionist thinking, that is, we find an opportunity to understand the world and intervene in it as part of nature, understanding ourselves as members of this web of life, of this interexistence. Our research was qualitative, exploratory, and experimental in nature, which also used cartographic inspiration and ethics for its development. It included a theoretical review of Regenerative Design and (Strategic) Design for Social Innovation and Sustainability; participant observation at the Institute for Regenerative Development; an immersion camp with a group of people in Serra da Cantareira/SP, for four days, for experimentation and metadesign; and in-depth interviews with the immersion participants. Through these processes, it was possible to initiate a proposition of Regenerative Strategic Design, with project principles and movements that were experienced and idealized from the research process. The principles of regenerative practice are interdependent and mutually reinforcing. They can be drivers of attitudes, processes and prospected scenarios. They are: Caring and enabling the emergence of integral health; Promoting autonomy in reciprocal relationships and circular flows; Seeking co-evolution by resignifying and developing valuable relationships with the ecosystem; Self-transformation from an ecosystemic vision; Developing commonality through eco dialogicity; and Developing the ecological knowledge of interexistence. The proposed regenerative strategic design movements are: mapping the singularity of the organization and place; mapping and prospecting its vocation - which would be the value-adding role of the supra and subsystems; and catalyzing the identification of capabilities and interventions that must be strengthened or developed so that the organization lives its singularity and vocation. This work sought to articulate and deepen the concept of regeneration and use Guattari's The Three Ecologies as a design work lens. The contributions of Regeneration and The Three Ecologies to Strategic Design are mainly an emphasis on acting from na ecosystemic view and the consideration of localized work – at the same time contributing na impact/value that reverberates positively across the scales of nested systems. Also, we tried to include, in the proposed design attitudes and modes, a look at the self-transformation of the designer subject – something that’s not explored in depth in the scope of Strategic Design.
Keywords: Regeneração; Design estratégico; Design regenerativo; Guattari; Regeneration; Strategic design; Regenerative design; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial